Air-water flow properties in stepped chutes with modified step and cavity geometries. (February 2018) - Zhang, Gangfu; Chanson, Hubert
Highlights: Extensive experimental investigation on air-water flow properties in stepped chutes with flat steps, partially blocked step cavities, and chamfers; Synchronised two-phase and total pressure measurements allowed individual examinations of air- and water-phase flow structures; A demarcation between turbulent flow features was found about where the void fraction was approximately 0.5; Partial cavity blockage reduces mutual sheltering between adjacent steps and leads to an increased presence of large-scale turbulent features in the mainstream; Chamfers results in a visually smooth overflow and air entrainment appears less intense. Abstract: Skimming air-water flow properties were investigated in a stepped chute configured with triangular steps, chamfered steps, and partially blocked step cavities. The turbulent interactions between air and water were examined using a synchronised system consisting of a dual-tip phase-detection probe and a pressure transducer mounted side-by-side. In comparison to uniform triangular steps, the chamfered steps were found to cause a reduction in air entrainment and an increase in mean velocity gradient next to the pseudo-bottom. Partial cavity blockages appeared to have little effect on air entrainment, but were linked to an increased presence of large-scale structures in the overflow, which likely resulted from a reduction in mutual sheltering between adjacent step elements. The results indicated that modifications of step and cavity geometries might have significant implications on stepped chute design.